Lacks and defects in the intents to achieve a general definition of disease - Peña, Adolfo (2002)
This second delivery is dedicated to point out and clarify some omissions that to our opinion the diverse proposals of disease concept exhibit. This critic hopes to orientate the interest toward the use of diverse concepts, theories, and metatheories that may contribute to the best execution of a theoretical model of disease. The analysis of the concepts, the utilization of the general theory of systems, mathematical models, and emergentism theory will demonstrate that to reach a general concept of disease is not possible only by going to the parcel of empiric investigation.